Ursolic acid reduces Adriamycin resistance of human ovarian cancer cells through promoting the HuR translocation from cytoplasm to nucleus. Issue 2 (3rd October 2020) - Li, Wei; Luo, Lanlan; Shi, Wenyin; Yin, Yujun; Gao, Shan
Abstract: Ursolic acid (UA) has been shown to suppress various tumor progression, however, its roles in Adriamycin resistance of human ovarian cancer (OC) cells are still unclear. This work aims to investigate the effects of UA on the Adriamycin resistance of human OC cells. Here, we constructed Adriamycin‐resistant OC SKOV3‐Adr cells and found that UA attenuated Adriamycin resistance in SKOV3‐Adr cells. Additionally, UA enhanced Adriamycin sensitivity in the parental SKOV3 and another OC cell line A2780 cells. Mechanistic studies showed that HuR mRNA level was similar between SKOV3 and SKOV3‐Adr cells, but the cytoplasmic expression of HuR protein was increased in SKOV3‐Adr cells compared with that in SKOV3 cells, and subsequently enhancing the mRNA stability of multidrug resistance gene 1 (MDR1). Moreover, UA had no effects on HuR expression, but promoted the cytoplasm‐nucleus translocation of HuR protein, decreased MDR1 mRNA stability and thus reduced MDR1 expression. Furthermore, overexpression of MDR1 rescued the effects of UA on Adriamycin resistance and sensitivity. This work reveals a novel HuR/MDR1 axis responsible for UA‐mediated attenuation on Adriamycin resistance in OC cells.